Influence of Recoater Speed on Powder Bed and Part Quality in Powder Bed Fusion of Metals Using a Laser Beam - Nick Hantke; Tim Robert Brocksieper; Tobias Grimm; Jan T. Sehrt (Metals)
The powder bed fusion of metals using a laser beam (PBF-LB/M) is an additive manufacturing process for the direct production of metal parts using powder as a starting material. The PBF-LB/M process consists of two main steps: the application of a new powder layer and the melting of the cross-sections of the parts in each layer. Laser exposure usually takes up a lot of time during a build process; however, the application of powder layers, also taking up a considerable amount of time, offers potential to shorten production times. In this work, a powder test rig that mimics the real flow conditions of a PBF-LB/M system is used to measure the quality of X3NiCoMoTi18-9-5 powder layers applied at different recoater speeds by determining the powder surface roughness. The same recoating settings are then used on a real PBF-LB/M system to produce samples and investigate their densities as a function of recoater speed. The results show that the recoater speed influences the surface of the applied powder bed and has an effect on the density of the manufactured samples. However, this influence decreases if only samples with a high relative density are considered.